2018
DOI: 10.5505/vtd.2018.07769
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of hyperforin and hypericin on inflammatory response in RAW 264.7 macrophages

Abstract: Acute inflammatory response represents an initial protective mechanism in the body (1,2). However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Also, Lee et al investigated the anti‐inflammatory effects of hyperforin and hypericin in lipopolysaccharide‐stimulated RAW macrophages and found that these compounds reduced iNOS and cyclooxygenase‐2 (COX‐2) gene expression in a dose‐dependent pattern (Lee et al, 2016). Berköz et al reported that hyperforin and hypericin reduced NO and PGE2 production, as well as a dosage‐dependent pattern of iNOS and COX‐2 gene expression in RAW 264.7 macrophages (Berköz et al, 2018) hence inflammation decreased (de Villiers et al, 2014).…”
Section: Wound Healing Properties Of H Perforatum L and Associated Me...mentioning
confidence: 99%
“…Also, Lee et al investigated the anti‐inflammatory effects of hyperforin and hypericin in lipopolysaccharide‐stimulated RAW macrophages and found that these compounds reduced iNOS and cyclooxygenase‐2 (COX‐2) gene expression in a dose‐dependent pattern (Lee et al, 2016). Berköz et al reported that hyperforin and hypericin reduced NO and PGE2 production, as well as a dosage‐dependent pattern of iNOS and COX‐2 gene expression in RAW 264.7 macrophages (Berköz et al, 2018) hence inflammation decreased (de Villiers et al, 2014).…”
Section: Wound Healing Properties Of H Perforatum L and Associated Me...mentioning
confidence: 99%
“…On the other hand, hypericin and hyperforin have been shown to reduce inflammatory prostaglandin E2 and COX-2 (cyclooxygenase-2) release from activated macrophages. It is reported that hypericin and hyperforin can be potential target drugs in cancer treatment due to their anti-inflammatory effect 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that hyperforin suppressed the activities of 5-lipoxygenase and cyclooxygenase (COX) enzymes which play a pivotal roles in regulation of inflammatory and immune responses (Albert et al, 2002). In another study on the antiinflammatory effects of hypericin and hyperforin, it has been reported that these substrates showed anti-inflammatory activity by decreasing prostaglandin E2 (PGE2) and nitric oxide (NO) production and COX-2 and inducible nitric oxide synthase (iNOS) gene expression (Berköz et al, 2018). HP has been reported to be effective antioxidant, antitumor and antimicrobial activities due to its flavonoid and some other phenolic components (Cakir et al, 2003;Milosevic et al, 2007;Pia Schiavone et al, 2014;Tungmunnithum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%